2009
DOI: 10.1007/s11661-009-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Void Nucleation and Growth in Dual-Phase Steel 600 during Uniaxial Tensile Testing

Abstract: Commercial dual-phase (DP) steel in sheet form and comprised of ferrite, martensite, and bainite was subjected to uniaxial tension up to fracture. The damage characteristics were studied through extensive quantitative metallography and scanning electron microscope (SEM) observations of polished sections and fracture surfaces of failed specimens. The observed void nucleation mechanisms include nucleation at the martensite/ferrite interface or triple junction (most predominant), nucleation due to the cracking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(113 citation statements)
references
References 40 publications
(65 reference statements)
12
95
0
Order By: Relevance
“…In addition to mechanisms that involve crack initiation and propagation within the martensite islands, failure of the ferrite-martensite (F-M) interface is another damage initiation mechanism that is reported for DP steels [5,7]. Uggowitzer and Stuwe [19] related this type of failure to the separation of inclusions from the martensite islands close to the interface with ferrite.…”
Section: Damage Mechanisms At the Boundariesmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to mechanisms that involve crack initiation and propagation within the martensite islands, failure of the ferrite-martensite (F-M) interface is another damage initiation mechanism that is reported for DP steels [5,7]. Uggowitzer and Stuwe [19] related this type of failure to the separation of inclusions from the martensite islands close to the interface with ferrite.…”
Section: Damage Mechanisms At the Boundariesmentioning
confidence: 99%
“…It is found that voids are associated with either non-metallic inclusions or martensite islands in DP steels [5]. The major void formation mechanisms reported [5][6][7] for DP steels include: 1) decohesion of the ferritemartensite interface, 2) fracture of martensite islands, and 3) voids generated in the martensite islands due to either the separation of prior austenite grain boundaries between adjacent martensite islands or the localized deformation within the martensite phase. The martensite cracking was found to be more frequent in a coarse martensite microstructure [5,7].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…8,[12][13][14] However, most of these works were carried out under limited experimental conditions such as a quasi-static tensile strain rate at room temperature. For further industrial application of the method, damage quantification must be performed at various conditions such as high deformation speed, cryogenic temperature etc.…”
Section: Optical Microscopy-based Damage Quantification: An Example Omentioning
confidence: 99%